Molecular Mechanisms Responsible for the Rescue Effects of Pamidronate on Muscle Atrophy in Pediatric Burn Patients - Pin, Fabrizio; Bonetto, Andrea; Bonewald, Lynda F.; Klein, Gordon L. (Frontiers in Endocrinology, 2019)
Not only has pamidronate been shown to prevent inflammation-associated bone resorption following burn injury, it also reduces protein breakdown in muscle . The aim of this study was to identify the molecular mechanisms responsible for muscle mass rescue in pamidronate-treated compared to placebo/standard of care-treated burn patients. Mature myotubes generated by differentiating murine C2C12 myoblasts, were exposed for 48h to 1% or 5% serum obtained from 3 groups of children: normal unburned, burned receiving standard of care after 30d, burned receiving standard of care and pamidronate also after 30d. Exposure to serum from burned patients caused dose-dependent myotube atrophy compared to normal serum as expected based on observations of muscle atrophy induced by burn injury in humans and animals. The size of C2C12 myotubes was partially protected upon exposure to the serum from patients treated with pamidronate, correrlating with the rescue of muscle size observed in these patients. At the molecular signaling level, serum from both pamidronate and non-pamidronate-treated burn patients increased pSTAT3/STAT3 and pERK1/2/ERK1/2 compared to normal serum with no significant differences between the two groups of burn patients, indicating elevated production of inflammatory cytokines. However, serum from pamidronate-treated patients restored the phosphorylation of AKT and mTOR and reduced protein ubiquitination when compared to burn serum alone, suggesting a prevention of muscle catabolism and a restoration of muscle anabolism. No differences were observed in the muscle autophagolysosome pathwary . However, myotube atrophy induced by burn serum was partially rescued after exposure to an anti-TGF beta-1/2/3 antibody, suggesting that this signaling pathway is partially responsible for the atrophy. Overall, these data suggest that bisphosphonate protection of bones from resorption during burn injury prevents the release of muscle pro-catabolic factors such as TGF beta into the circulation.